(untitled) (Dublin, 1981)
The preparation of this book was greatly facilitated by a large number of people around the world who assisted in tracking down the ever-elusive" grey material" who helped dispel numberous,...
Keywords: Natural resources,Environmental policy,Nguồn tài nguyên thiên nhiên; Management.,Quản lý